A Retrospective Analysis on the Effects and Complications of Endoscope-Assisted Transoral Approach and Lateral Cervical Approach in the Resection of Parapharyngeal Space Tumors. (23rd September 2022) - Guo, Danni; Sun, Changling; Yin, Xiao; Qu, Hongyang; Dai, Bingyi; Hu, Lin; Zhou, Chen; Du, Xiaodong
Abstract : Objective . To observe and compare the effects and complications of endoscope-assisted transoral approach and lateral cervical approach in the resection of parapharyngeal space (PSS) tumors. Methods . From January 2013 to September 2021, 69 patients with parapharyngeal space tumors in the Affiliated Hospital of Jiangnan University were divided into the control group ( n = 37) and the observation group ( n = 32) according to the mode of operation. The tumors in the parapharyngeal space were resected by the lateral cervical approach in the control group, and the tumors in the parapharyngeal space were removed by endoscopy-assisted transoral approach in the observation group. The general clinical data and operation conditions of the two groups, including operative blood loss, operation time, drainage volume and drainage time, hospital stay, perioperative pain degree, and tumor resection rate were collected and analyzed statistically. The patients were followed up for 6 months, and the complications of the two groups were recorded. Results . Compared with the control group, the operation time in the observation group was significantly shorter, and the amount of intraoperative bleeding in the observation group was significantly less than that in the control group, and the difference was statistically significant (P < 0.05 ). The postoperative drainage was less and the hospital stay in the observation group was shorter than that in the control group, and the difference was statistically significant (P < 0.05 ). There was no significant difference in tumor resection rate between the two groups. The visual analog scale (VAS) score on the 1st and 3rd day after operation in the observation group was lower than that in the control group. After treatment, some patients in the two groups had complications such as nerve injury, dysphagia, difficulty in mouth opening, massive hemorrhage, and parotid fistula. The total incidence of complications in the observation group was lower than that in the control group, and the difference was statistically significant (P < 0.05 ). Conclusions . The effect of the endoscope-assisted transoral approach is similar to that of the lateral cervical approach in the resection of tumors in parapharyngeal space, but the endoscope-assisted transoral approach has shorter operation time, less intraoperative bleeding, and less postoperative drainage. The indwelling time and hospital stay of the drainage device were shorter than those of the patients with transcervical approach, and the perioperative stress response of patients with endoscope-assisted transoral approach is mild, which is beneficial to the physical and mental recovery of the patients.